WORKSHOP LATIHAN OTOT WAJAH DAN LIDAH UNTUK MENINGKATKAN KEMAMPUAN BICARA PADA ANAK DENGAN CEREBRAL PALSY - Gita Dewi; Dewi Tara Anjani; Ghita Nurul Fadhilah; Shiane Hanako Sheba (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2025)
Cerebral palsy is a neurological condition that often causes weakness in the facial muscles and tongue, resulting in speech difficulties in children. This community service program aims to increase parents' and caregivers' knowledge of active oral motor exercises (OME) through interactive workshops held at Al Islam Polytechnic in Bandung in January 2026. The workshop involved demonstrations and discussions on facial and tongue muscle exercises in preparation for implementing structured OME therapy. A total of 17 parents or caregivers of children with cerebral palsy participated. Knowledge levels were evaluated using pre- and post-test questionnaires consisting of five closed-ended questions related to the definition, benefits, examples, frequency, and risks of OME. Data were analyzed using descriptive statistics and paired t-tests. Results showed a significant increase in participants' knowledge, with the average score increasing from 82.6% on the pre-test to 98.8% on the post-test. These findings indicate that interactive workshops are effective in increasing understanding of OME among parents and caregivers. It is recommended that similar workshops be integrated into public health programs to support early speech intervention in children with cerebral palsy. Keywords: cerebral palsy; oral motor exercises; speech ability; facial muscle training; community workshop; Service to society.